2017
DOI: 10.12965/jer.1735046.523
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature response to unilateral training measured with infrared thermography

Abstract: This study aimed to identify the skin temperature (Tsk) behavior to understand the acute cross-effect after unilateral training of lower-limbs. Seventeen healthy young men (weight, 75.2±5.5 kg; height, 1.8±0.1 m; age, 22.5±1.6 years) were divided into two groups: high-trained (n=8) and low-trained (n=9). All participants performed: (a) one-repetition maximum (1RM) testing protocol on the leg press, (b) a unilateral training protocol (4×10 repetitions at 70% of 1RM for leg press and 4×10 repetitions at 50% of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
5
17
0
Order By: Relevance
“…Some authors have even found an absence of significant cross-education results when strength training was performed on the nondominant side [12], results that are in line with ours regarding nonsignificant temperature increases when the NMES was applied on the nondominant side.…”
Section: Dominancesupporting
confidence: 90%
See 2 more Smart Citations
“…Some authors have even found an absence of significant cross-education results when strength training was performed on the nondominant side [12], results that are in line with ours regarding nonsignificant temperature increases when the NMES was applied on the nondominant side.…”
Section: Dominancesupporting
confidence: 90%
“…Blickenstorfer et al [34], using functional magnetic resonance, demonstrated an activation of the contralateral primary motor cortex, premotor cortex, and cerebellum.Although most studies have investigated the phenomenon of cross-education in the area of strength, our research shows a cross-education effect on Tsk. Escamilla-Galindo et al [12] and Manca et al [35] state that the causes of the increase in temperature in the leg that is not exercised are not clear, since other parameters such as phospho-creatinekinase levels or electromyography (EMG), were not measured in their study in parallel with temperature.…”
Section: Cross-educationmentioning
confidence: 99%
See 1 more Smart Citation
“…So, this combination of exercises seems to have been responsible for the increase in temperature found in the aforementioned ROI. Our data is aligned with that in previous studies [37][38][39][40] , however, it is in disagreement with others 41,42 .…”
Section: Discussionsupporting
confidence: 75%
“…The research conducted by Escamilla-Galindo et al 32 sought to analyze the behavior of skin temperature to understand the acute cross-effect after unilateral lower limb training in two different groups, one with young people with high RT experience and one with low experience. The main results showed that, regardless of the limb (exercised versus not exercised), differences were observed in the skin temperature of the regions of interest after the training session.…”
Section: Castro Vicente Pinheiro Lima ------------------------------mentioning
confidence: 99%